2020
DOI: 10.3390/metabo10120509
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Lipidomics and Transcriptomics Reveals Reprogramming of the Lipid Metabolism and Composition in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is fundamentally a metabolic disease. Given the importance of lipids in many cellular processes, in this study we delineated a lipidomic profile of human ccRCC and integrated it with transcriptomic data to connect the variations in cancer lipid metabolism with gene expression changes. Untargeted lipidomic analysis was performed on 20 ccRCC and 20 paired normal tissues, using LC-MS and GC-MS. Different lipid classes were altered in cancer compared to normal tissue. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 56 publications
(45 reference statements)
1
58
0
Order By: Relevance
“…In support of the involvement of bioenergetic alterations in CCRCC biology, overexpression of NDUFA4L2 in CCRCC blocks oxidative phosphorylation, reduces ROS production, and increases cellular antioxidants levels promoting progression and drug resistance [40]. Recently, Lucarelli et al identified a lipid metabolism reprogramming associated with a switch in adipogenic gene signatures in CCRCC, with accumulation of very long-chain FAs and PUFAs, sustained by overexpression of SCD1 and ELOVLs [41].…”
Section: Discussionmentioning
confidence: 99%
“…In support of the involvement of bioenergetic alterations in CCRCC biology, overexpression of NDUFA4L2 in CCRCC blocks oxidative phosphorylation, reduces ROS production, and increases cellular antioxidants levels promoting progression and drug resistance [40]. Recently, Lucarelli et al identified a lipid metabolism reprogramming associated with a switch in adipogenic gene signatures in CCRCC, with accumulation of very long-chain FAs and PUFAs, sustained by overexpression of SCD1 and ELOVLs [41].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of lipid metabolism described in ccRCC include increased uptake of extracellular lipids [ 58 ], tumor grade-dependent increased de novo synthesis of fatty acids [ 59 ] and decrease in fatty acid beta-oxidation [ 60 , 61 , 62 ], and the pathognomonic accumulation of large intracellular lipid deposits [ 8 , 9 ]. Untargeted lipidomic analyses of ccRCC compared with normal kidney tissue revealed a characteristic “ccRCC lipidomic signature”, including increased levels of cholesteryl esters and triacylglycerols, as well as lower levels of phospholipids (other than phosphatidylcholines) and polyunsaturated fatty acids [ 63 , 64 ]. Furthermore, integrated lipidomic and transcriptomic analyses showed that alterations in cellular lipid composition in ccRCC were accompanied by multiple consistent changes in gene expression, including increased CD36 (fatty acid uptake), stearoyl-CoA desaturase and fatty acid elongases 2 and 5 (fatty acid synthesis), reduced carnitine palmitoyltransferase 1A (CPT1A, rate-limiting enzyme for the transport of fatty acids into mitochondria for beta-oxidation), as well as perilipin 2 (triglyceride storage in lipid droplets) [ 64 ].…”
Section: Lipid Metabolic Reprogramming In Ccrccmentioning
confidence: 99%
“…Untargeted lipidomic analyses of ccRCC compared with normal kidney tissue revealed a characteristic “ccRCC lipidomic signature”, including increased levels of cholesteryl esters and triacylglycerols, as well as lower levels of phospholipids (other than phosphatidylcholines) and polyunsaturated fatty acids [ 63 , 64 ]. Furthermore, integrated lipidomic and transcriptomic analyses showed that alterations in cellular lipid composition in ccRCC were accompanied by multiple consistent changes in gene expression, including increased CD36 (fatty acid uptake), stearoyl-CoA desaturase and fatty acid elongases 2 and 5 (fatty acid synthesis), reduced carnitine palmitoyltransferase 1A (CPT1A, rate-limiting enzyme for the transport of fatty acids into mitochondria for beta-oxidation), as well as perilipin 2 (triglyceride storage in lipid droplets) [ 64 ]. These alterations likely play important roles in ccRCC biology, and are logical therapeutic targets for ongoing and future investigation.…”
Section: Lipid Metabolic Reprogramming In Ccrccmentioning
confidence: 99%
“…This is accompanied by several transcriptomic events, some regulated by HIFs. Integrated lipidomic and transcriptomic analysis revealed increased accumulation of polyunsaturated fatty acids (PUFA) and overall fatty acid desaturation and elongation [82]. Interestingly, obesity is a risk factor in ccRCC, but paradoxically, patients with ccRCC who are obese have better prognosis [83][84][85].…”
Section: Metabolomicsmentioning
confidence: 99%